The Effect of Advertising Disclosure Language and Celebrity Endorsement on Tiktok on Purchasing Decisions for Fashion Outfit Products - Lestari, Moye; Purwanto, Kelik; Elida Putri, Dini; Ferdinal, Alex (Green Publisher, 2023)
Today's growing promotional media greatly affects the digital world and product marketing on purchasing decisions. The Effect of Advertising Disclosure Language and Celebrity Endorsment on Purchasing Decisions for Fashion Outfit products is research within the scope of management science. The aim is to analyze and examine the effect of advertising disclosure language and celebrity endorsment on tiktok on purchasing decisions for fashion outfit products for teenagers, especially students at dharmas indonesia university. The method used is quantitative method. data collection using a questionnaire. Data analysis techniques with Validity test, Instrument reliability test, Correlation analysis, Hypothesis test, Multiple Regression analysis, Classical Assumption test, Multiple linear Regression analysis. The population in this study were 1,811 respondents and the samples in this study were 292 who were students of Dharmas Indonesia University. The results of this study: 1) Advertising Disclosure Language affects the purchase decision of Fashion Outfit products; and 2) Celebrity Endorsment has an effect on purchasing decisions for Fashion Outfit products.